2006
DOI: 10.3950/jibiinkoka.109.587
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study on Deep Neck Infection

Abstract: Deep neck infection (DNI) remains an emergent and life-threatening otolaryngologic disease. We examined 69 patients, 52 men and 17 women, with DNI, who were treated in our hospital between January 1995 and December 2004.The mean age of the patients with DNI was 50.0 years and the peak incidence was in the sixth decade. Twenty patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Second, several studies have found that patients with diabetes spend longer periods of time in the hospital than those without . In the present meta‐analysis, the mean difference between hospitalization periods was significantly longer in patients with diabetes than in nondiabetic patients, with significant heterogeneity among studies (Table ).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Second, several studies have found that patients with diabetes spend longer periods of time in the hospital than those without . In the present meta‐analysis, the mean difference between hospitalization periods was significantly longer in patients with diabetes than in nondiabetic patients, with significant heterogeneity among studies (Table ).…”
Section: Discussionmentioning
confidence: 63%
“…After excluding 9 reports addressing duplicate results, 16 reports were noted to have addressed the clinical features of deep neck infection without clarifying differences between diabetic and nondiabetic groups of patients. Quantitative synthesis was performed on the remaining 20 eligible studies . The study by Srivanitchapoom et al categorized 177 patients into those with diabetes mellitus or human immunodeficiency virus (HIV; n = 34) and an immunocompetent host group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation